2020
DOI: 10.5551/jat.54221
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Thrombectomy for Posterior Circulation Occlusion: A Comparison of Outcomes with the Anterior Circulation Occlusion – A Meta-Analysis

Abstract: There is no randomized controlled trial to compare the effectiveness and safety of mechanical thrombectomy (MT) to intravenous thrombolysis in patients with posterior circulation occlusion (PCO). Hence, we firstly performed a meta-analysis to investigate the outcomes of MT in PCO and then compared these outcomes to anterior circulation occlusion (ACO) to provide fundamental data to further studies. Methods: We searched the PubMed, EMBASE, and Cochrane Library from dates of inception to June 2019 for relevant s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
37
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 27 publications
4
37
1
Order By: Relevance
“…Studies by previous meta-analyses showed no statistical difference between PCLVO and ACLVO in both recanalization success and 90 day functional outcome (19,20). A comparable likelihood of obtaining successful recanalization (Figure 8) and 90 day favorable functional outcome (Figure 10) was also found in our meta-analysis that included more recent studies.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Studies by previous meta-analyses showed no statistical difference between PCLVO and ACLVO in both recanalization success and 90 day functional outcome (19,20). A comparable likelihood of obtaining successful recanalization (Figure 8) and 90 day favorable functional outcome (Figure 10) was also found in our meta-analysis that included more recent studies.…”
Section: Discussionsupporting
confidence: 84%
“…To the best of our knowledge, until the conduction of this metaanalysis, there had been two prior meta-analyses comparing MT in anterior and posterior circulation stroke with both studies, however, focusing on MT safety and efficacy outcomes (19,20). This study, conducted independently from previous studies, included more recent literature on MT in PCLVO and ACLVO and, in a detailed meta-analysis, further sought to compare demographics and baseline characteristics, risk factors, as well as recanalization treatment profiles between the two brain circulations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accounting for only 1-4% of ischemic strokes, basilar artery occlusion (BAO) is a rare but devastating subtype of stroke, causing over 70% of deaths or a substantial part of severe disability in survivors (1), which has obtained abundant attention recently (2). In 2020, the results of the BEST randomized controlled trial and our real-world multicenter BASILAR research illustrated the improvement of mechanical thrombectomy (MT) for BAO (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…In 2020, the results of the BEST randomized controlled trial and our real-world multicenter BASILAR research illustrated the improvement of mechanical thrombectomy (MT) for BAO (3,4). However, despite this progress, the current understanding of the prognostic imaging markers of BAO in response to MT was limited, due to the challenges faced in performing multi-modal magnetic resonance imaging (MRI), which were caused by the rare prevalence of BAO and the low usage rate of MRI in a preoperative examination (2).…”
Section: Introductionmentioning
confidence: 99%